Mengungkap Makna Kematian Soeharto pada Cover Tempo - Indiwan Seto Wahju Wibowo (Universitas Multimedia Nusantara, 2010)
Soeharto's death becomes a major topic of Tempo Magazine ,issue No.50/XXXVI/04-10 February, 2008 specially in the magazine's cover. And this cover is so controversial as describes Soeharto as Jesus at the last supper an iconic Christianity symbol. The last supper is the final meal that according to Christian belief, Jesus shared with his apostles in Jerusalem before his crucifixion. This research is about to describe what Tempo Magazine play their role as social control and it's rivalitation towards Soeharto. The purpose of this Research is to find out the meaning behind the Tempo Magazine Cover as describes Soeharto – the former Indonesia President- as Jesus. Kata kunci : makna kematian Soeharto, Semiotika Charles Sander Peirce, Kualitatif